Socio-demographic and basal characteristics in women victims of violence in two communities of Huánuco - Manrique de Lara Suárez, Digna A. (2019)
The objective of the study was to determine the sociodemographic and baseline characteristics of women victims of intimate partner violence in two communities of Huánuco. It was developed through an observational, prospective and cross-sectional study; of descriptive level. The population were women from the town center of Supte and Las Moras Human Settlement and the sample of 43 people who met the selection criteria, sampling was not probabilistic in the intended modality; the instruments were the interview guide and a knowledge test adapted to the Likert scale. The results showed a greater percentage in the sociodemographic characteristics in the age of 18 to 24 years 35% and 21.74%; 80% cohabiting civil status and 86.90%; housewife occupation 75% and 78.30%; grade incomplete primary education 30% and 26.1% and secondary incomplete 40% and 21.7% respectively for each location. In the baseline characteristics, the marital life time, number of children, years lived with violence, forms of violence and level of knowledge in human, sexual and reproductive rights and gender equality were evaluated. The perceived forms of violence were low emotional violence, low physical violence in Supte and high in Moors and low sexual violence in Supte and high in Moors. The level of knowledge in their sexual and reproductive rights is from low to high Concluding that the appreciation of intimate partner violence in women depends to a large extent on the level of knowledge.